Rethinking cynicism: Parrhesiastic practices in contemporary workplaces - Karfakis, Nikos; Kokkinidis, George (My University, 2011)
This paper looks at the concept of cynicism as a form of employees' resistance to managerial control. Some studies tend to view cynicism as a potentially conservative and self-defeating form of resistance that inherently thwarts the possibilities for confronting managerial control. We argue, however, that cynicism can also be viewed as a disruptive force, if we look at it in its original meaning. Drawing inspiration from the works of Foucault and Sloterdijk, we pay attention to the ethics of antiquity and more specifically to parrhesia, with the aim of rethinking cynicism and emphasizing its potential applicability to organizational life. © 2011 Taylor & Francis.
Keywords: cynicism; kynicism; parrhesia; power; resistance